Risk of colorectal cancer following CT‐verified acute diverticulitis: a nationwide population‐based cohort study. (9th May 2020) - Azhar, N.; Buchwald, P.; Ansari, H. Z.; Schyman, T.; Yaqub, S.; Øresland, T.; Schultz, J. K.
Abstract: Aim: Routine colonoscopy to exclude colorectal cancer (CRC) after CT‐verified acute diverticulitis is controversial. This study aimed to compare the incidence of CRC in patients with acute diverticulitis with that in the general population. Method: Patients with an emergency admission for diverticular disease to any Norwegian hospital between 1 January 2008 and 31 December 2010 were included through identification in the Norwegian Patient Registry using International Classification of Diseases (ICD‐10) codes K57.1‐9. To estimate the age‐specific distribution of CT‐verified acute uncomplicated diverticulitis (AUD) and acute complicated diverticulitis (ACD) in this nationwide study population, numbers from the largest Norwegian emergency hospital were used. Patients diagnosed with CRC within 1 year following their admission for acute diverticulitis were detected through cross‐matching with the Cancer Registry of Norway. Based on both Norwegian age‐specific incidence of CRC and estimated age‐specific distribution of CT‐verified diverticulitis, standard morbidity ratios (SMRs) were calculated. Results: A total of 7473 patients with emergency admissions for diverticular disease were identified (estimated CT‐verified AUD n = 3523, ACD n = 1206); of these 155 patients were diagnosed with CRC within 1 year. Eighty had a CT‐verified diverticulitis at index admission [41 AUD (51.3%); 39 ACD (49.7%)]. Compared with the general population, the SMR was 6.6 following CT‐verified AUD and 16.3 following ACD, respectively. Conclusion: In the first year after CT‐verified acute diverticulitis, especially after ACD, the risk of CRC is higher than in the general population. This probably represents misdiagnosis of CRC as acute diverticulitis. Follow‐up colonoscopy should be recommended to all patients admitted with acute diverticulitis.